Adult Behavior of Tirumala limniace (Lepidoptera: Danaidae). Issue 1 (22nd June 2015) - Li, Chengzhe; Wang, Fanyan; Chen, Xiaoming; Zhou, Chengli; Yao, Jun
Abstract : Tirumala limniace Cramer as an ornamental butterfly is utilized in butterfly garden, in this article we study their adult activities include flight, foraging, courtship, mating, and oviposition. We found that males spent 22.1% of its time flying, 14.1% foraging, 63.8% in courtship and mating. And females spent 30.8% of its time flying, 10.1% foraging, 57.1% in courtship and mating, and 2% ovipositing. Adults emerged from pupae when temperatures were above 23.5°C and eclosion took only ∼1 min, typically followed by a small amount of flight on the first day. Flight activity peaked from the ninth to the thirteenth day after eclosion, and there were two daily peak flight times: 10:00–13:00 and 15:00–18:00. The peak of flower-visiting activity was from the eighth to the thirteenth day after eclosion, and there were two daily peak foraging times: 11:00–12:00 and 16:00–17:00. Flight and foraging frequency and time were positively correlated and both were closely related to temperature, with very little flight or foraging below 18°C and an increase at temperatures above 22°C. Courtship and mating took place on the sixth day after eclosion, while oviposition occurred the following day. Oviposition occurred over 8 d, and the shortest time of a single oviposition was 2 s. The average life expectancy of males was 16.5 d, while that of females was 15 d.